Dental care seeking behaviour of children in a rural Nigerian community (2016)
There is sparse information about oral health seeking behaviour of children in rural areas of developing countries. The aim of the study was to determine the dental care seeking behaviour of children attending the first rural based community oral health centre in Nigeria. A retrospective review of records of patients aged 16 years or younger treated at the Primary Oral Health Care Centre in Ibarapa, Nigeria over six years was conducted. Data on sociodemographic characteristics of the patients, pattern of presentation and their oral hygiene practices were collected and processed using SPSS. A total of 239 paediatric patients were seen during the period with a mean age of 9.7 ± 4.4 years and 132 (55.2%) were males. The majority, 225 (94.1%), were presenting for the first time. All the children sought dental care for one problem or the other and the most common reasons for seeking care were: tooth ache in 105 (43.9%), trauma in 30 (12.6%) and perceived unclean mouth in 20 (8.4%) patients. Older children were more likely to seek dental care because of pain (p < 0.001), while younger children sought care principally on account of trauma (p < 0.001) and the under 5 years were seen more often for gum ache (p = 0.006). The majority, 175 (73.2%), used toothbrush and 182 (76.2%) cleaned their teeth once daily. None of the children presented for routine check-up, rather, consultation was as a result of dental problems with toothache being the most common reason